Design and Optimization of Microstrip Patch Antenna for UWB Applications Using Moth–Flame Optimization Algorithm - Singh, Anshuman; Mehra, R. M.; Pandey, V. K. (Wireless personal communications, 2020)
The design of microstrip patch (MP) antenna using Moth–Flame optimization (MFO) algorithm for UWB applications is presented in this article. MP antennas are designed to operate in dual and multi-band application as it possess the following advantages such as low cost, light weight and easy installation. To reduce the microstrip patch cross-polarized radiation and to attain the essential radiation parameters, the MP antenna is designed with a defected ground structure. The substrate of liquid crystal polymer is used here to reduce the material cost and the applicable geometry parameters are used to improve antenna performance. The MFO optimized antenna represents 50 mm × 50 mm compact size, which improves the performance of antenna. However, the simulation procedure is done by the MATLAB tool along with high frequency structure simulator for parameter optimization and performance analysis respectively. The operational bandwidth of the antenna is 3.1 GHz and the return loss is − 20 dB that covers the UWB (3.1–10.6 GHz) applications. The simulation outcomes exhibit good impedance bandwidth, radiation pattern, directivity, and relatively constant gain over the entire band of frequency comparing with the earlier methods. Finally, the proposed system can be a better option for the design of microstrip antenna in the communication system, to cover Bluetooth operations, Wi-Fi, Wi-MAX, Telemedicine and UWB applications.